Sensory and Physicochemical Characteristics of Manyung (Arius thalassinus) Kekian High Fiber with the Addition of Eucheuma cottonii Seaweed - Meisya Asri Widiyanti; Lukita Purnamayati; Romadhon Romadhon (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Kekian is a processed product from fish meat added with seasoning, fillers and binders then formed and wrapped with tofu skin. Kekian has a low dietary fiber so that the addition of seaweed porridge can be used to increase the content of dietary fiber in kekian. The purpose of this study was to determine the effect of adding different seaweed porridge (Eucheuma cottonii) to characteristics of manyung (Arius thalassinus) kekian and determine the best seaweed porridge to the best kekian fish characteristics. The research method used was experimental laboratories using a completely randomized design of one factor is concentration of the addition of porridge (0%, 20%, 30% and 40%) with 3 replications. Sensory value data were analyzed by the Kruskal-Wallis test, while tests of dietary fiber, air content, protein content, water holding capacity and gel strength were analyzed using ANOVA. The results showed that the difference in the addition of seaweed porridge had a significant effect (P